The red locust - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Insect Science and its Application. Volume 19, No 4. 397 pp. 1999. A special issue of the International Journal of Tropical Insect Science. ISSN 0191-9040 US$ 60 E 70.35 (Institutional rate) US$ 40 E 46.90 (Individual rate) Insect Science a